Prototype Design of Electronics Laboratory Door Security for PTE Department Using Arduino Nano Based E-KTP - Safaat, Tutur; Lastya, Hari Anna; Fachri, Muhammad Rizal (PTE FTK UIN Ar-Raniry, 2025)
The electronics laboratory of the PTE department still faces issues with conventional keys, limiting access control. To address this, a prototype door security system using e-KTP as an access key was developed through a quantitative experimental method. A system trial was carried out to evaluate the performance of the solenoid and LCD components. Seven e-KTP samples were selected using random probability sampling. The system was built using an ATmega328 microcontroller on an Arduino Nano, with RFID as input and LCD and solenoid as outputs. An admin card was designated to manage user access, including registration and deletion. Testing results revealed an authentication success rate of 87.5%. The distance and response time of RFID reading showed 85.71% accuracy, with a response time of under 2 seconds and a maximum effective scanning distance of 2.5 cm. Additionally, metal was identified as the main obstacle to RFID signal transmission, with a success rate of 83.33% when tested with barrier materials. These results demonstrate the effectiveness and feasibility of the e-KTP-based door security prototype for the PTE electronics laboratory